Endurance Exercise Mobilizes Developmentally Early Stem Cells into Peripheral Blood and Increases Their Number in Bone Marrow: Implications for Tissue Regeneration - Krzysztof Marycz; Katarzyna Mierzejewska; Agnieszka Śmieszek; Ewa Suszynska; Iwona Malicka; Magda Kucia; Mariusz Z. Ratajczak (Stem Cells International)
Endurance exercise has been reported to increase the number of circulating hematopoietic stem/progenitor cells (HSPCs) in peripheral blood (PB) as well as in bone marrow (BM). We therefore became interested in whether endurance exercise has the same effect on very small embryonic-like stem cells (VSELs), which have been described as a population of developmentally early stem cells residing in BM. Mice were run daily for 1 hour on a treadmill for periods of 5 days or 5 weeks. Human volunteers had trained in long-distance running for one year, six times per week. FACS-based analyses and RT-PCR of murine and human VSELs and HSPCs from collected bone marrow and peripheral blood were performed. We observed that endurance exercise increased the number of VSELs circulating in PB and residing in BM. In parallel, we observed an increase in the number of HSPCs. These observations were subsequently confirmed in young athletes, who showed an increase in circulating VSELs and HSPCs after intensive running exercise. We provide for the first time evidence that endurance exercise may have beneficial effects on the expansion of developmentally early stem cells. We hypothesize that these circulating stem cells are involved in repairing minor exercise-related tissue and organ injuries.